The Grb2/Mek Pathway Represses Nanog in Murine Embryonic Stem Cells - Hamazaki, Takashi (American Society for Microbiology, 2006)
The homeobox gene Nanog is a key intrinsic determinant of self renewal in embryonic stem (ES) cells, and its repression leads ES cells to selectively differentiate into primitive endoderm. Although Nanog repression occurs at the outermost layer of ES cell aggregates independent of the leukemia inhibitory factor (LIF)/STAT3 pathway, it is largely undetermined what external cues and intracellular signals cause the event. Of interest, addition of the tyrosine phosphatase inhibitor, sodium vanadate, selectively repressed Nanog transcription without any detectable changes in upstream transcriptional regulators Oct3/4 and Sox2. Furthermore, sodium vanadate induced primitive endoderm differentiation, even in the inner cells of ES cell aggregates. Expression of Gata6 and Zfp42, two putative downstream Nanog effectors, was also increased and decreased by the addition of sodium vanadate, respectively, but these changes were eliminated by exogenous Nanog expression. The effects of sodium vanadate were abrogated by Grb2 deficiency or by the addition of the Mek inhibitor, PD98059. Indeed, PD98059 prevented Nanog repression induced by ES cell aggregation as well. Furthermore, transfection of a constitutive active Mek mutant into ES cells induced Nanog repression and primitive endoderm differentiation. These data indicate that the Grb2/Mek pathway primarily mediates Nanog gene repression upon ES cell differentiation into primitive endoderm.